FOOD ORIENTATION OF AGRICULTURAL PRODUCTION IN THE CONTEXT OF THE CORONAVIRUS PANDEMIC - Anvarovich, Hakimov Akbarjon; Abdujabborovna, Botirova Rakhimakhon; Kutbiddinovich, Sirojiddinov Ikromiddin (The journal of contemporary issues in business and government, 2021)
The article examines the issues of strengthening the food orientation of agriculture, as well as the possibility of developing production and increasing the export potential of horticulture, viticulture and vegetable growing in the Namangan region of Uzbekistan.